The Influence of Digital Customer Experience and Security Perseptions on Customer Trust at PT. Sinar Artha Semesta - Yudho Bagas Reynaldi; Eni Suharti; Cahyani Kurniastuti (West Science Business and Management, 2026)
(Introduction) The advancement of digital technology has transformed the way companies interact with customers. The digital customer experience is a crucial factor in creating customer satisfaction and loyalty in online services. Furthermore, security perceptions plays a crucial role in building customer trust when using digital platforms. (Background Problems) Many customers are still hesitant to use digital services because they are worried about the quality and security perseptions of the services. (Novelty) Previous studies have addressed digital customer experience and security perceptions separately. However, this study, which analyzes the combined influence of these variables on customer trust in the context of digital services, is still limited. (Research Methods) This study uses a quantitative approach, data was collected through questionnaires distributed to 84 respondents using probability sampling techniques and data processing was assisted by Microsoft Excel and SPSS software version 29. (Finding/Results) The results of the study show that 1.) Digital Customer Experience has a positive and significant impact on Customer Trust; 2.) Security Perseptions has a positive and significant impact on Customer Trust; 3.) Digital Customer Experience and Security Perseptions simultaneously have a positive and significant impact on Customer Trust. In addition, it has a contribution of 50.1% while the remainder is influenced by other variables not studied. (Conclusion) Improving the quality of the Digital Customer Experience and Security Perseptions can increase Customer Trust in PT. Sinar Artha Semesta. Therefore, the company needs to continuously optimize the Digital Customer Experience and Security Perseptions aspects to maintain and enhance Customer Trust.